Peningkatan Jiwa Kewirausahaan Ibu-ibu PKK Melaui Pelatihan Diversifikasi Olahan Buah Siwalan di Kecamatan Paciran - Hidayati, Novi Itsna; Maghfiroh, Khoirin; Ernawati, Ernawati; Lidyana, Novita (Abdi Panca Marga, 2023)
Siwalan tree is a versatile plant, one of which can produce juice which is used as a drink with a high taste and distinctive fragrance characteristics. Through processed differentification, Siwalan Fruit can produce various products that can be commercially useful. In Sumurgayam Village, Paciran District, on average, women only work as housewives. The purpose of this activity is to cultivate entrepreneurial skills through the processing of food made from siwalan fruit to PKK mothers in Sumurgayam Village, Paciran District, Kabipaten Lamongan. This activity time will be held for 3 days on February 20-22, 2023. The place where this activity was held was in Sumurgayam Village, Paciran District, Lamongan Regency. This activity uses the method of lectures, discussions, questions and answers and provides training on diversification of various processed dishes made from Siwalan Fruit to PKK mothers. The results obtained from this activity were PKK mothers, knowledge and skills that increased by more than 75% of the total participants in processing Siwalan Fruit into various high-value preparations. The more difficult the process of making process, the lower the percentage of skills of trainees.